X‐Ray Detectors: Sensitive and Fast Direct Conversion X‐Ray Detectors Based on Single‐Crystalline HgI2 Photoconductor and ZnO Nanowire Vacuum Diode (Adv. Mater. Technol. 5/2020). Issue 5 (11th May 2020) - Zhang, Zhipeng; Zhang, Zhaojun; Zheng, Wei; Wang, Kai; Chen, Huanjun; Deng, Shaozhi; Huang, Feng; Chen, Jun
Abstract : In article number 1901108, Feng Huang, Jun Chen, and co‐workers design a direct conversion X‐ray detector based on a HgI2 crystal and a ZnO nanowire vacuum diode to overcome the current runaway effect at high operating electric field and improve the detection sensitivity. The detector shows a sensitivity of 6.8 × 10 3 μCGyair −1 cm −2 and a response time of 0.24 ms. The proposed X‐ray detector is promising for the application of low dose X‐ray detection.